Distinct Functional Connectivity Signatures of Impaired Social Cognition in Multiple Sclerosis - Golde, Sabrina; Heine, Josephine; Pöttgen, Jana; Mantwill, Maron; Lau, Stephanie; Wingenfeld, Katja; Otte, Christian; Penner, Iris-Katharina; Engel, Andreas K.; Heesen, Christoph; Stellmann, Jan-Patrick; Dziobek, Isabel; et al. (Frontiers in Neurology, 2020)
Objective: Multiple Sclerosis (MS) is characterized by impairments in basic cognitive functions such as information processing speed as well as in more complex, higher order domains such as social cognition. However, as these deficits often co-occur, it has remained challenging to determine whether they have a specific pathological basis or are driven by shared biology. Methods: To identify neural signatures of social cognition deficits in MS, data were analyzed from n=29 patients with relapsing-remitting MS and n=29 healthy controls matched for age, sex, and education. We used neuropsychological assessments of information processing speed, attention, learning, working memory, and relevant aspects of social cognition (theory of mind, emotion recognition (ER), empathy) and employed neuroimaging of CNS networks using resting state functional connectivity. Results: MS patients showed significant deficits in verbal learning and memory, as well as implicit ER. Performance in these domains was uncorrelated. Functional connectivity analysis identified a distinct network characterized by significant associations between poorer ER and lower connectivity of the fusiform gyrus (FFG) with the right lateral occipital cortex that also showed lower connectivity in patients compared to controls. Moreover, while ER was correlated with MS symptoms such as fatigue and motor/sensory functioning on a behavioral level, FFG connectivity signatures of social cognition deficits showed no overlap with these symptoms. Conclusions: Our analyses identify distinct functional connectivity signatures of social cognition deficits in MS, indicating that these alterations may occur independently from those in other neuropsychological functions.